Industrial-Scale Production of Mycotoxin Binder from the Red Yeast Sporidiobolus pararoseus KM281507 - Tapingkae, Wanaporn; Srinual, Orranee; Lumsangkul, Chompunut; Doan, Hien Van; Chiang, Hsin-I; Manowattana, Atchara; Boonchuay, Pinpanit; Chaiyaso, Thanongsak (Journal of fungi (Basel), 2022)
Red yeast Sporidiobolus pararoseus KM281507 has been recognized as a potential feed additive. Beyond their nutritional value (carotenoids and lipids), red yeast cells (RYCs) containing high levels of β-glucan can bind mycotoxins. This study investigated the industrial feasibility of the large-scale production of RYCs, along with their ability to act as a mycotoxin binder. Under a semi-controlled pH condition in a 300 L bioreactor, 28.70-g/L biomass, 8.67-g/L lipids, and 96.10-mg/L total carotenoids were obtained, and the RYCs were found to contain 5.73% (w/w) β-glucan. The encapsulated RYC was in vitro tested for its mycotoxin adsorption capacity, including for aflatoxin B1 (AFB1), zearalenone (ZEA), ochratoxin A (OTA), T-2 toxin (T-2) and deoxynivalenol (DON). The RYCs had the highest binding capacity for OTA and T-2 at concentrations of 0.31–1.25 and 0.31–2.5 µg/mL, respectively. The mycotoxin adsorption capacity was further tested using a gastrointestinal poultry model. The adsorption capacities of the RYCs and a commercial mycotoxin binder (CMB) were comparable. The RYCs not only are rich in lipids and carotenoids but also play an important role in mycotoxin binding. Since the industrial-scale production and downstream processing of RYCs were successfully demonstrated, RYCs could be applied as possible feed additives.